ANALYSIS OF MULTICULTURAL EDUCATION VALUES IN ISMUBA TEXTBOOKS (AL-ISLAM, MUHAMMADIYAH STUDIES, AND ARABIC): A CONTENT ANALYSIS STUDY - Vikri Aflaha Qomari; Dede Rosyada; Erba Rozalina Yulianti (Academic Bright Collaboration, 2025)
This study aims to critically analyze the extent to which multicultural education values ​​are integrated into the ISMUBA textbooks for grade XI at Muhammadiyah educational institutions. Although Muhammadiyah schools are open to students from diverse backgrounds, all students are implicitly required to take ISMUBA, raising questions about whether these materials reflect multicultural principles. This study used a qualitative method with a library research approach. Primary data consisted of ISMUBA textbooks for grade XI, while secondary data included relevant books and scientific articles. The analysis was guided by the dimensions of multicultural education proposed by James A. Banks and a constructivist perspective. The findings indicate that multicultural education values are implicitly integrated into the textbooks, including content integration, knowledge construction, equity pedagogy, and prejudice reduction, although these values are not explicitly presented as dedicated multicultural topics. This study is limited to textbook content analysis and does not examine classroom implementation, which may influence how these values are interpreted in practice. This study concludes that, conceptually, ISMUBA textbooks align with key dimensions of multicultural education but require critical interpretation by educators to ensure effective implementation in diverse learning contexts.